2012
DOI: 10.1159/000343782
|View full text |Cite
|
Sign up to set email alerts
|

The p.G146A and p.P125P Polymorphisms in the Steroidogenic Factor-1 <b><i>(SF-1)</i></b> Gene Do Not Affect the Risk for Hypospadias in Caucasians

Abstract: Hypospadias is a frequent congenital malformation in boys and is characterized by incomplete fusion of the urethral folds. The steroidogenic factor-1 (SF-1, NR5A1) gene plays a key role in hypothalamic-pituitary-steroidogenic organ development, and has previously been reported to be mutated in individuals with 46,XY disorder of sex development. Here, we investigated the role of SF-1 in hypospadias, a milder form of 46,XY disorder of sex development. We performed direct sequencing analysis of the SF-1 gene in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Similar to our functional assays, Arg313Cys showed reduced transactivation on the promoters of the AMH and CYP11A1 genes [37]. Although Arg313 is located in the highly conserved helix 5 of the ligand-binding domain, this same position has also been described for an Arg313His change (c.838G>A) in males with hypospadias [38], [39]. Thus, position Arg313 of SF-1 may be a hot spot for mutations.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our functional assays, Arg313Cys showed reduced transactivation on the promoters of the AMH and CYP11A1 genes [37]. Although Arg313 is located in the highly conserved helix 5 of the ligand-binding domain, this same position has also been described for an Arg313His change (c.838G>A) in males with hypospadias [38], [39]. Thus, position Arg313 of SF-1 may be a hot spot for mutations.…”
Section: Discussionsupporting
confidence: 84%
“…However, the relative importance of different NR5A1 polymorphisms in hypospadias may depend on ethnicity. Variants in NR5A1 were frequently associated with hypospadias in Chinese patients, but not in Swedish Caucasians [Adamovic et al, 2012]. Two novel NR5A1 mutations with aberrant biological activity were also found in Egyptian patients [Tantawy et al, 2014] (table 2).…”
Section: Genes Implicated In Testis Development Masculinisation and mentioning
confidence: 99%
“…However, the father of the proband, who showed the same polymorphism, was not affected by any reproductive disorder, supporting other evidence that Gly146Ala polymorphism leaves transcriptional activity unaltered [15,26]. Recently, analysis of a large case series and controls concluded that no association between Gly146Ala polymorphism and hypospadias is operative, at least in Caucasians [29]. Thus, its causative role remains doubtful.…”
Section: Discussionmentioning
confidence: 60%